1989
DOI: 10.1002/hep.1840090311
|View full text |Cite
|
Sign up to set email alerts
|

Immunization of experimental animals with dihydrolipoamide acetyltransferase, as a purified recombinant polypeptide, generates mitochondrial antibodies but not primary biliary cirrhosis

Abstract: The availability of recombinant mitochondrial autoantigens may permit the experimental study of the pathophysiology of primary biliary cirrhosis. Previously, we demonstrated that high-titer antibodies to the 74 kD mitochondrial autoantigen dihydrolipoamide acetyltransferase could be generated when BALB/c mice were immunized with purified recombinant protein. Based on these data, we attempted an 8-month study to induce antibodies and liver dysfunction by immunizing AKR/J, C3H/J and CBA/HeJ mice as well as rats,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(49 citation statements)
references
References 23 publications
2
44
0
3
Order By: Relevance
“…AMAs do not appear themselves to be pathogenetic because induction of AMA in laboratory animals does not lead to bile duct damage. 31 Similarly, neither the presence nor titer of AMA and the other PBC-specific autoantibodies (gp210 and the multiple nuclear dots antibodies) correlate with the histologic features of PBC recurrence. 32 Biliary epithelial cells from the native livers of patients with PBC but not with other conditions have plasma membrane expression of the antigen recognised by AMA (the E2 component of the dihydrolipoamide acetyl transferase).…”
Section: What Does Recurrence Of Disease Mean For the Pathogenesis Ofmentioning
confidence: 95%
“…AMAs do not appear themselves to be pathogenetic because induction of AMA in laboratory animals does not lead to bile duct damage. 31 Similarly, neither the presence nor titer of AMA and the other PBC-specific autoantibodies (gp210 and the multiple nuclear dots antibodies) correlate with the histologic features of PBC recurrence. 32 Biliary epithelial cells from the native livers of patients with PBC but not with other conditions have plasma membrane expression of the antigen recognised by AMA (the E2 component of the dihydrolipoamide acetyl transferase).…”
Section: What Does Recurrence Of Disease Mean For the Pathogenesis Ofmentioning
confidence: 95%
“…Although this possibility must be qualified by the possibility that AMA may indeed be detectable in such cases if more sensitive laboratory techniques are used, it is supported by the lack of correlation of disease activity with AMA titer, and uncertain association of AMA with disease in animal models of PBC. 79,80 However, given that B-and T-cell epitopes of PDC-E2 overlap, 81 it is unclear why the association of AMA and PBC is not absolute: it remains to be seen whether T cells from patients with AMA-negative PBC react to the same epitope or derived peptides as those from patients with AMA, or whether lack of AMA positivity in PBC is conferred by different class II HLA loci. The introduction of HLA-antigen tetramer technology in probing T-cell receptor specificity may be of particular value in this setting.…”
Section: Pathologic Implications Of Overlap Syndromesmentioning
confidence: 99%
“…In an initial study, Krams et al 32 found that immunization of a variety of laboratory animals with recombinant E2 resulted in the generation of circulating AMA, but granulomatous cholangitis was not detectable. These observations suggested that the AMA do not directly induce an immune response to normal biliary epithelial cells.…”
Section: Ama and Pathogenesis Of Pbcmentioning
confidence: 99%